Ein neuer metrischer Traktat und das Studium der pindarischen Metrik in der Philologie der Paläologenzeit - Günther, Hans Christian. (Mnemosyne, Supplements, 1998)
An edition of a newly discovered Byzantine treatise of Pindaric metre, this work first discusses its date, place of origin and places it into the context of metrical studies in Byzantine philology. It then examines its relevance for the manuscript transmission of Pindar thereby providing new insights into numerous problems of the textual tradition of this author. Moreover the Pindaric text of the Paleologan era is examined in a systematic fashion with a view to the methods and achievements of individual Byzantine scholars. A concluding chapter discusses the characteristics and the achievements of Byzantine philology in the history of classical scholarship. An appendix provides new descriptions of many Pindaric manuscripts.